Effectiveness of Cervical Cerclage in Women with Cervical Incompetence - Kaukab Naheed (Journal of Rawalpindi Medical College, 2008)
Background: To evaluate the effectiveness of cervical cerclage in cervical incompetence Methods: This prospective observational study included a total of 46 women with single alive gestation at 14 to 24 weeks. They either had previous history suggestive of cervical incompetence or cervical changes associated with cervical incompetence as found on transabdominal scan. McDonald cervical cerclage was placed around the cervix between 14 – 24 weeks of gestation. Results: Term delivery rate was 95.4 %. Preterm delivery rate before 34 weeks of gestation was 4.6 % and the mean gestational age at delivery was 35 weeks with mean prolongation of delivery interval 28 weeks after the application of cerclage. The mean birth weight was 2800 grams. Neonatal survival was 96% and neonatal morbidity was 4 %. Conclusion: Our results effectively prove the effectiveness of cervical cerclage in cervical incompetence.